Vibration Characteristics Induced by Cavitation in a Centrifugal Pump with Slope Volute - Ning Zhang; Minguan Yang; Bo Gao; Zhong Li (Shock and Vibration)
Cavitation is one of the instability sources in centrifugal pump, which would cause some unexpected results. The goal of this paper was to analyze the influence of cavitation process on different frequency bands in a centrifugal pump with slope volute. And special attention was paid to low frequency signals, which were often filtered in the reported researches. Results show that at noncavitation condition, vibration level is closely related to flow structure interior pump. At partial flow rates, especially low flow rates, vibration level increases rapidly with the onset of rotating stall. At cavitation condition, it is proved that cavitation process has a significant impact on low frequency signals. With cavitation number decreasing, vibration level first rises to a local maximum, then it drops to a local minimum, and finally it rises again. At different flow rates, vibration trends in variable frequency bands differ obviously. Critical point inferred from vibration level is much larger than that from 3% head drop, which indicates that cavitation occurs much earlier than that reflected in head curve. Also, it is noted that high frequency signals almost increase simultaneously with cavitation occurring, which can be used to detect cavitation in centrifugal pump.